DYNAMICS OF IMMUNOLOGICAL INDICATORS IN THERAPY OF EXPERIMENTAL TOXIC HEPATITIS IN RATS WITH SAFFLOWER OIL (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2025)
This study assessed the effects of safflower oil on cytokine dynamics, angiogenesis factors, and metabolic regulators in an experimental rat model of toxic hepatitis. IL-1β levels were 1.47-fold higher on day 7 and 2.04-fold higher on day 14 compared to intact animals (p